Pemberdayaan Masyarakat Desa Dalam Penanganan Trauma Dasar Melalui Pelatihan Pertolongan Pertama Berbasis Keluarga Di Desa Binaan - Yuni Suharnida Lubis; Aulia Zulda Nasution; Zahra Salsabila (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
The main issue faced by the community of Tanjung Anom Village, especially in Dusun I, is the lack of knowledge and basic skills in providing first aid for minor trauma incidents at the household level. This community service activity aims to enhance family capacity in trauma management through community-based training. The method used is Participatory Action Research (PAR) with a community organizing approach, starting from preliminary observation, focus group discussions, training sessions, to post-activity evaluation. The results showed that the training positively impacted residents' knowledge and skills, led to the formation of local trauma cadres, and fostered new social structures supporting community preparedness for emergencies. The activity also encouraged behavioral change and collective awareness regarding the importance of basic trauma care in households.